Remoção da cartilagem articular associada ou não a implante homógeno ou enxerto autógeno de osso esponjoso em cães submetidos à artrodese atlantoaxial Joint cartilage removal associated or not to homologous implant or autologous cancellous bone graft in dogs submitted to atlantoaxial arthrodesis - Rafael Festugatto; Alexandre Mazzanti; Alceu Gaspar Raiser; Fernanda Souza Barbosa da Silva; Tiago Luis Eilers Treichel; João Paulo Mori da Cunha; Fernanda Cátia Muler; Jaine Soares de Paula Vasconcellos; Denise de Castro Veiga; Bruno Leite dos Anjos (Ciência Rural, 2013)
O objetivo deste estudo foi avaliar o grau de fusão articular e formação óssea na articulação atlantoaxial de cães submetidos à artrodese após a remoção da cartilagem articular associada ou não ao implante homógeno ou enxerto autógeno de osso esponjoso. Foram utilizados 12 cães, adultos, distribuídos aleatoriamente em três grupos iguais. Grupo I (GI): realizada apenas a remoção da cartilagem articular e imobilização articular com pinos e resina acrílica. Grupo II (GII): feita a remoção da cartilagem articular e imobilização da articulação, seguida da colocação e modelagem do implante ósseo esponjoso homógeno entre as superfícies articulares. Grupo III (GIII): foi realizado o mesmo procedimento do GII, mais o enxerto ósseo esponjoso autógeno no local determinado. Realizaram-se exames radiográficos em todos os animais aos 30, 60 e 90 dias de pós-operatório (PO). Aos 90 dias de PO foi feita a eutanásia para o emprego do teste de palpação manual, avaliação tomográfica e histopatológica. Para análise estatística da associação entre o grau de fusão articular, aplicou-se o Teste Qui-quadrado de independência. Os resultados dos testes foram avaliados pela significância exata e considerados significantes a 5% (P<0,05). Pelo teste de palpação manual e pelas imagens tomográficas, não houve diferença entre os grupos aos 90 dias de PO. A análise radiográfica da articulação atlantoaxial mostrou que o grau de fusão era semelhante entre os tratamentos entre os tempos de evolução. Com relação ao estudo histopatológico da articulação atlantoaxial dos cães, decorridos 90 dias de PO, foi verificado que a proliferação óssea no grupo I apresentou grau de intensidade proporcional, no grupo II, 75% leve e 25% acentuada e, no grupo III, 25% moderada e 75% acentuada. Não existe diferença quanto ao grau de fusão articular e formação óssea quando a técnica de artrodese atlantoaxial em cães for associada ao enxerto de osso esponjoso autógeno ou implante homógeno. A remoção da cartilagem articular isoladamente é uma alternativa eficiente e apresenta resultados semelhantes, quando associada ao enxerto autógeno ou implante homógeno. The aim of this study was to evaluate the degree of joint fusion and bone formation in dogs undergoing atlantoaxial arthrodesis after removal of articular cartilage associated or not to implant homogenous or autogenous cancellous bone. Twelve dogs, weighing between 8 and 12kg were randomly divided into three groups. Group I (GI) performed only the removal of joint cartilage and joint immobilization with acrylic resin and pins. Group II (GII): after removel of joint cartilage and articular immobilization was performed modeling and placement of homogenous cancellous bone at the given location. The volume of homograft placed in the joint was measured using a precision balance and all animals received the same amount. Group III (GIII): this was the same procedure as GI, however, was used autogenous cancellous bone graft at the given location. Radiographic examinations were performed on all animals at 30, 60 and 90 days postoperatively. At 90 days of PO was carried out euthanasia of animals for testing of manual palpation and CT evaluation and histological. Samples were kept in solution in 10% buffered formaldehyde for fixation for a minimum of 72 hours and after, decalcified in formic acid and sodium citrate for subsequent processing and included in paraffin. Sections were stained with hematoxylin-eosin for light microscopy evaluation. Statistical analysis of the association between the degree of joint fusion assessed by manual palpation, the digitized radiographic images and CT scans and treatment groups, we applied the Chi-square test of independence. The test results were evaluated by the exact significance and considered statistically significant at 5% significance (P<0.05). By manual palpation test and by the CT images can be seen that there was no statistically significant difference between groups at 90 days postoperatively. Radiographic analysis of the atlantoaxial joint showed that the degree of fusion was similar among treatments, no statistical difference at 30, 60 and 90 days postoperatively. Regarding the histopathological study of atlantoaxial joint of dogs after 90 days postoperatively was found that bone formation in group I had 25% of each intensity (absent, mild, moderate, severe) in group II, 75% lighter and 25% sharp and in group III, 25% moderate and 75% severe. It can be concluded that the use of graft homogenous preserved in 98% glycerin in dogs undergoing atlantoaxial fusion method is a viable alternative for treatment of atlantoaxial instability. There is no difference in the degree of joint fusion and bone formation when the technique of atlantoaxial arthrodesis in dogs is associated with autogenous cancellous bone graft or implant homogenous. The removal of articular cartilage alone is an effective and shows similar results to the use of autograft or homogenous implant.